Rancang Bangun Sistem Monitoring dan Klasifikasi Lingkungan Hidup Larva Lalat Tentara Hitam (Hermetia Illucens) dengan Metode K-Nearest Neighbor (K-NN) - Amri Yahya; Rizal Maulana; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The process of biodegradation is the activity of using a microorganism to carry out the process of handling waste quickly. Microorganisms that can handle waste efficiently are black larvae. Environmental quality of larvae supports the process of biodiversity. The environmental quality monitoring system uses several sensors and a microcontroller which is packaged in the form of a monitoring and classification system. Classification of the k-NN method produces three classes namely "Optimal", "Medium", and "Bad" with input of some environmental quality of larvae. Internet of Things (IoT) is used to send monitoring and classification system data results to an Android application. The results of the k-NN classification test showed 91.3%. Computational time testing gets time with an average of 4275ms on a system. Testing the sending of data from the system to Firebase and Firebase to the Android application results that 100% of data is sent according to the monitoring and classification system data.